2011
DOI: 10.1007/s00404-011-2120-6
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative activity of lignans against the breast carcinoma cell lines MCF 7 and BT 20

Abstract: The human lignans enterodiol and enterolactone are more biologically active than their precursors secoisolariciresinol and matairesinol, and may be defined as the real drugs in cancer prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 24 publications
1
16
0
1
Order By: Relevance
“…The preference of estradiol over enterolactone for the ER could ensure that enterolactone will not perform its anti-proliferative and apoptotic effects, thus tumor growth is increased in these mice. In vitro studies have shown that enterolactone can inhibit tumor growth in MCF-7 cell lines, with high concentrations of enterolactone inhibiting cellular proliferation by 97% compared to 60% by matairesinol; however at low concentrations (1 × 10 −5 to 1 × 10 −7 mol/L) a stimulatory effect was seen [21]. In vivo studies with MCF-7 xenograft models have shown that mice fed a soy protein diet had increased tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…The preference of estradiol over enterolactone for the ER could ensure that enterolactone will not perform its anti-proliferative and apoptotic effects, thus tumor growth is increased in these mice. In vitro studies have shown that enterolactone can inhibit tumor growth in MCF-7 cell lines, with high concentrations of enterolactone inhibiting cellular proliferation by 97% compared to 60% by matairesinol; however at low concentrations (1 × 10 −5 to 1 × 10 −7 mol/L) a stimulatory effect was seen [21]. In vivo studies with MCF-7 xenograft models have shown that mice fed a soy protein diet had increased tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…The preventive role of PhyEs if assumed during adolescence was also supported by the result of a study showing that intake of PhyEs during adolescence among Ontario women was associated with a reduced risk of developing breast cancer (Anderson et al, 2013). Intake of lignans was also associated with a reduced risk of developing breast cancer (Abarzua et al, 2012), moreover enterodiol and enterolactone, alone or in combination with tamoxifen, seemed to reduce human breast cancer cell adhesion, invasion and migration in vitro (Chen and Thopmson, 2003). However, the estrogenic behavior of enterolignans is not fully clear.…”
Section: Natural Xenoestrogensmentioning
confidence: 99%
“…For many isolated phytoestrogens, anti-cancerous effects have been documented in vitro and in vivo. Secoisolariciresinol, matairesinol [16] and genistein [17] are known to inhibit cell growth in MCF7 cell cultures. Several animal studies have shown a reduction of tumour growth, e.g.…”
Section: Discussionmentioning
confidence: 99%